O pojęciu hellenizacji - Mrugalski, Damian (Verbum Vitae, 2021)
The term Hellenization refers to the spread of Greek culture and its adoption by non-Greek peoples, in the era that begins with the conquests of Alexander the Great (i.e. from the second half of the 4th century BC onwards). The term is defined likewise or similarly in many modern dictionaries and encyclopedias of antiquity. The term became problematic when, in the second half of the 19th century and the first half of the 20th century, historians of religion associated it with certain kinds of value judgements and sometimes even ideology. Therefore, some contemporary scholars propose abandoning the concept of ‘Hellenization’ in the study of antiquity, or to replace it with others that would describe the phenomena occurring in the Hellenistic era neutrally. This article shall present an overview of selected positions with regard to the notion of ‘Hellenization’ itself, and attempt to answer the question whether this ideologically loaded term can be avoided in contemporary research on the Hellenistic Age